Trastornos pódales en bovinos de sistemas de producción doble propósito en el Departamento Córdoba, Colombia - Jaime Álvarez P (Revista Colombiana de Ciencia Animal - RECIA, 2017)
The objetive was determining the frequency of pedal upheavals in double purpose bovines in the Córdoba department. A study was done of cross section using 170 greater cows of three year selected at random in different property which were evaluated by means of the accomplishment of the clinical examination of the hooves, determining normality or then abnormality that these displayed and in agreement with the found injury, it was identified and characterized. The frequency of pedals upheavals in Córdoba department was of 64.70% of the total of the studied sample. 30.59% of the studied animals displayed alteration of the relation 2:1 wall-heel and 47.05 % displayed some type of podal pathology. The found pedals pathologies were: Hoof in corkscrew (36.47%), digital granuloma (17.06%), septic pododermatitis (4.71%) and interdigital callus (2.35%) the incidence of lameness was of 78.75% with respect to the animals that displayed pathologies and 37.05% with relation to the total of the sample. In addition was dependency between the type of land with relation to the podal upheaval and independence between podales adjustments and presence of footbaths with relation to the podal adjustment.